ex. y = (x^2 + 3) / (x - 1)
cant seem to isolate the x squared. also the eq. can be rewritten as
y = (x+1) + (4 / (x-1))
help would be appreciated
Hello, mzez!
$\displaystyle \text{Solve for }x\!:\;y \:=\: \frac{x^2 + 3}{x - 1}$
We have: .$\displaystyle y(x-1) \:=\:x^2+3 \quad\Rightarrow\quad xy - y \:=\:x^2+3 \quad\Rightarrow\quad x^2 - yx + (y+3) \:=\:0 $
Quadratic Formula: .$\displaystyle x \;=\;\frac{y \pm \sqrt{y^2 - 4(y+3)}}{2} $
. . . . . . Therefore: .$\displaystyle x \;=\;\frac{y \pm \sqrt{y^2 - 4y - 12}}{2}$